034 MR spectroscopy and dynamic contrast-enhanced perfusion studies in two SARS-CoV-2 infection patients with neurological complications and no other MR abnormalities. (23rd August 2021) - Zhang, Xin; Chaganti, Joga; Brew, Bruce
Abstract : Objectives: To understand NeuroCovid pathogenesis by using MR spectroscopy and dynamic contrast perfusion in 2 SARS-COV-2 patients with neurological complications. Methods: MR spectroscopy (MRS) and dynamic contrast-enhanced perfusion (k-trans), which is a sensitive marker of blood brain barrier (BBB) damage, were performed in 2 patients with respiratory viral PCR confirmed SARS-CoV-2 infection and 2 local controls. The MRS and k-trans results were also compared with published controls. Results: Case 1 was a 73-year-old man with critical SARS-CoV-2 infection requiring 4 days of mechanical ventilation. He had persistent anosmia, anorexia and apathy; saccadic pursuit eye movements, action tremor in the left hand and a positive right-sided palmomental reflex. These changes normalised by day 30 of presentation. MRI brain was undertaken on day 37. Case 2 was a 61-year-old man with critical SARS-CoV-2 infection requiring 43 days of mechanical ventilation. He was slow to wake post weaning of sedation and had residual mild cognitive impairment. MRI brain was undertaken on day 62 of presentation. No abnormalities were detected on T1, T2, FLAIR, DWI, SWI MR sequences. However, for both patients there was diffuse increase in k-trans especially in the frontal cortex and increased glutamate-glutamine MRS signal intensities in the pons compared to controls. Conclusions: The MRS and k-trans changes show excitotoxicity and BBB damage, in the absence of stroke or MR-defined white matter injury. They suggest a direct effect of SARS-CoV-2 on the brain. These MR techniques can offer insight into NeuroCovid pathogenesis when patients are no longer infectious. References: Heye AK, Culling RD, Valdés Hernández MC, Thrippleton MJ, Wardlaw JM. Assessment of blood-brain barrier disruption using dynamic contrast-enhanced MRI. A systematic review. Neuroimage Clin 2014;6 :262–274. Langer DL, Rakaric P, Kirilova A, Jaffray DA, Damyanovich AZ. Assessment of metabolite quantitation reproducibility in serial 3D-(1)H-MR spectroscopic imaging of human brain using stereotactic repositioning. Magn Reson Med 2007;58(4):666–673. Chang L, Munsaka SM, Kraft-Terry S, Ernst T. Magnetic resonance spectroscopy to assess neuroinflammation and neuropathic pain. J Neuroimmune Pharmacol 2013;8(3):576–593.